Exposure To Authentic Audiovisual Programs In Informal Setting And Language Learning - Bahrani, Taher (The Turkish Online Journal of Design Art and Communication, 2012)
Today, various audio-visual technologies are developing by sharing and showing a variety of programs to both instruct and entertain different audience. These developments offer many possibilities for teachers to utilize different programs as various sources of authentic language input to construct activities for enhancing language learning. In the same line, the present paper aimed at providing empirical evidence on the effect of exposure to various audio-visual programs on language proficiency of differentiated language proficiency levels language learners in informal setting. To this end, 75 language learners majoring in TESL were assigned to 3 language proficiency levels based on the scores obtained by them from an IELTS pre-test: low (N=25), intermediate (N=25), and upper-intermediate (N=25) levels. During the study all the participants were asked to have exposure to their preferred audio-visual program(s) in informal setting and keep track of the amount and type of exposure. At the end of the study, another IELTS test was administered to all the participants to find out which language proficiency level(s) language learners could improve their language proficiency more. The results of the post-test were indicative of the fact that intermediate and upper-intermediate language learners improved their language proficiency more. The data obtained from the self-report sheets also showed that the intermediate and upper-intermediate participants had more exposure to news than other programs.
Keywords: Mass Media; Authentic; Language Input; Language Proficiency; Kitle İletişim Araçları; Otantik; Dil Girişi; Dil Yeterliliği